Statistical evaluation of information received by means of discrete canal without memory - Aksomaitis, A. (Lithuanian Mathematical Journal, 1963)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. Аксомайтис. Статистическая оценка количества информации в дискретном канале без памяти A. Aksomaitis. Diskretinio be atminties kanalo informacijos kiekio statistinis įvertinimas